1984
DOI: 10.2307/1939460
|View full text |Cite
|
Sign up to set email alerts
|

Radio‐Tracking Confirms a Unique Diurnal Pattern of Spatial Occurrence in the Parasitic Brown‐Headed Cowbird

Abstract: Brood—parasitic Brown—headed Cowbirds (Molothrus ater) in the eastern Sierra Nevada of California, breed and feed in almost totally disjunct areas that reflect local optima for finding host nests and food, respectively. Radio—tracking showed that five females and four of eight males spent mornings in host—rich habitats such as forests and then commuted 2.1—6.7 km to one or more prime feeding sites such as horse corrals and bird feeders for the rest of the day. The four noncommuting males, which were all yearli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 26 publications
(31 reference statements)
4
157
1
Order By: Relevance
“…Obviously, more research is needed to isolate why we found sexspecific effects of captivity on Hp volume in M. a. obscurus despite a lack of sex-specific Hp size in wild birds of the population we studied. Future studies should consider subspecies and within-subspecies population differences as cowbird space use appears to depend on a number of habitat, habitat use, and population size dimensions (Darley, 1982(Darley, , 1983Dufty, 1982;Lowther, 1993;Rothstein, Verner, & Steven, 1984;Rothstein et al, 1986). Precedents for such within-species population differences are found in black-capped chickadees (P. atricapilla).…”
Section: Cowbird Population Differencesmentioning
confidence: 99%
“…Obviously, more research is needed to isolate why we found sexspecific effects of captivity on Hp volume in M. a. obscurus despite a lack of sex-specific Hp size in wild birds of the population we studied. Future studies should consider subspecies and within-subspecies population differences as cowbird space use appears to depend on a number of habitat, habitat use, and population size dimensions (Darley, 1982(Darley, , 1983Dufty, 1982;Lowther, 1993;Rothstein, Verner, & Steven, 1984;Rothstein et al, 1986). Precedents for such within-species population differences are found in black-capped chickadees (P. atricapilla).…”
Section: Cowbird Population Differencesmentioning
confidence: 99%
“…Females then generally search for and apparently select the next nest for parasitism, although nothing is known about whether females "line up" nests for parasitism. By late morning, females have generally left the host nesting area and travelled to areas to forage, eventually flying to a roost site in the evening (e.g., Rothstein et al 1984;Curson et al 2000). Before sunrise the next morning, females fly directly to the selected nest, approach it "stealthily," often in the dark (Scott 1991;Sealy et al 2000;Sealy and McMaster 2004), and parasitize it within a few seconds (Sealy et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Female cowbirds are active but generally silent in breeding ranges in the morning (Rothstein et al 1984). They are highly mobile and perch or fly high above the ground (Rothstein et al 1984), presumably searching for hosts' nests.…”
Section: Habitat Usementioning
confidence: 99%
“…They are highly mobile and perch or fly high above the ground (Rothstein et al 1984), presumably searching for hosts' nests. Breeding ranges are rarely used for foraging (Rothstein et al 1984), but Yokel (1986) found that cowbirds feed opportunistically on cicadas in breeding ranges in a California riparian habitat. Morning ranges of males frequently overlap female breeding ranges (Yokel 1986), and males often travel with females (Rothstein et al 1984).…”
Section: Habitat Usementioning
confidence: 99%
See 1 more Smart Citation